Effect of reconstituted discoidal high density lipoproteins on lipid mobilization in RAW 264.7 and CHOK1 cells - Toledo, Juan Domingo (2012)
Reconstituted discoidal high density lipoproteins (rHDL) resemble nascent HDL, which are formed at the early reverse cholesterol transport steps, and constitute the initial cholesterol (Chol) acceptors from cell membranes. We have used different sized rHDL containing or not Chol, to test their abilities to promote cholesterol and phospholipid efflux from two different cell lines: Raw 264.7 macrophages and CHOK1 cells. All rHDL and lipid-free apolipoprotein A-I (apoA-I) were found to be bound to CHO and RAW cells. In RAW cells, a positive correlation between cellular binding and Chol removal was found for 78 and 96 Å rHDL. Chol-free rHDL were more effective than Chol-containing ones in binding to RAW cells and promoting Chol removal. These results were more evident in the 96 Å rHDL. On the other hand, rHDL binding to CHO cells was relatively independent of disc size and Chol content. In spite of the fact that apoA-I and rHDL promoted Chol efflux from both cellular lines, only in CHOK1 cells this result was also associated to decrease Chol esterification. Among choline-containing phospholipids, only phosphatidylcholine (PC) (but not sphingomyelin) was detected to be effuxed from both cellular lines. With the only exception of Chol-free 96 Å discs, the other rHDL as well as apoA-I promoted PC efflux from RAW cells. Chol-containing rHDL were more active than Chol-free ones of comparable size to promote PC efflux from RAW macrophages. Regarding CHO cells, only apoA-I and Chol-free 78 Å rHDL were active enough to remove PC. J. Cell. Biochem.